The Long Cross type of Æthelred II in Finnish finds: Some comments on Ian Stewart’s paper ‘How did Anglo-Saxon coins reach Finland? - Talvio, Tukka (Hikuin, 1985)
No other numismatic material from Finnish finds has been as thoroughly studied as the Anglo-Saxon coins. In the 1890s Otto Alcenius, a retired school-master with wide scholarly interests, laid plans for the publication of Finland’s Viking-Age coin finds, commencing with a volume on their Anglo-Saxon element. When he died in 1913, his Anglosachsiska mynt funna i Finland was with the printer. Unfortunately the manuscript was not completed, and the printing was discontinued, but in 1921 there appeared a similar work by another author, Carl Axel Nordman’s Anglo-Saxon Coins Found in Finland. In 1978 the same material was published anew, with additions, as volume 25 of Sylloge of Coins of the British Isles.